Curricula Designer with Enhanced ECSF Analysis - Hajný, Jan; Sikora, Marek; Adamos, Konstantinos; Di Franco, Fabio (ACM, 2023)
In late 2022, the novel European Cybersecurity Skills Framework (ECSF) was officially released by the European Union Agency for Cybersecurity (ENISA). It aims to connect cybersecurity education and training with practical needs of the job market. In particular, it maps role profiles, that reflect jobs, to the knowledge and skills they require. One of the first tools that demonstrated ECSF is the Curricula Designer web application that guides cybersecurity study program administrators in designing and analyzing their curricula. In this paper, we present a major update of the Curricula Designer tool. We develop a novel method for course scoring and quantitative analysis of curricula based on the European Credit Transfer and Accumulation System (ECTS) credits. We describe the underlying methods and show their practical implementation into the publicly-available web application. Furthermore, we update the definitions of the Skills, Knowledge and Role Profiles according to the latest ECSF definition and present the mappings in comprehensive matrices in the appendices.

In late 2022, the novel European Cybersecurity Skills Framework (ECSF) was officially released by the European Union Agency for Cybersecurity (ENISA). It aims to connect cybersecurity education and training with practical needs of the job market. In particular, it maps role profiles, that reflect jobs, to the knowledge and skills they require. One of the first tools that demonstrated ECSF is the Curricula Designer web application that guides cybersecurity study program administrators in designing and analyzing their curricula. In this paper, we present a major update of the Curricula Designer tool. We develop a novel method for course scoring and quantitative analysis of curricula based on the European Credit Transfer and Accumulation System (ECTS) credits. We describe the underlying methods and show their practical implementation into the publicly-available web application. Furthermore, we update the definitions of the Skills, Knowledge and Role Profiles according to the latest ECSF definition and present the mappings in comprehensive matrices in the appendices.
Curricula Designer with Enhanced ECSF Analysis
Keywords: Education; training; tools; cybersecurity; profiles; skills; knowledge; Education; training; tools; cybersecurity; profiles; skills; knowledge